Studi Numerik Dengan Model Empat Parameter Untuk Memprediksi Daya Luaran Dari Panel Surya (P3M Politeknik Negeri Cilacap, 2020)
Solar panel is one of the most promising renewable energies technology that can be an alternative of the fossil fuel energy. Furthermore, an accurate model to simulate the solar panel efficiency and power output is required. In this study, four parameters model is used to simulate the power output of the solar panel. Four parameters are extracted from single diode equation by using Matlab software then validate with manufacturer datasheet and one-day experiment condition. The error value from datasheet and experiment are 0.03% and 3.54%, respectively. Findings show that four parameters model is accurate. In the future, this result can be taken as a valuable reference for researcher and industrial to modelling energy output of the solar panel.